Preparing the high school classroom for migrant english language learners (2014)
In United States schools, the rate of immigrant English language learners is rapidly rising, affecting the lives of both students and teachers. This article will discuss the best ways to facilitate the students’ language learning in a school setting; the type of structure, goals, and standards that can be expected; as well as ways to change the preconceived notions of teachers. The implications of this work are significant. We are obligated to support our English language learners with up-to-date teaching approaches and modifications to harness their strengths and enable them to succeed as learners in an English-speaking setting.En las escuelas de los Estados Unidos, el índice de estudiantes inmigrantes que están aprendiendo inglés crece rápidamente, lo cual afecta las vidas de estudiantes y maestros. En este artículo se analiza la mejor forma de ayudar a los estudiantes en su proceso de aprendizaje, mientras se encuentran en un ambiente de adquisición de lenguaje; incluyendo el tipo de estructura, metas y estándares que se pueden esperar, además de cambiar nociones preconcebidas por parte de los profesores. Las implicaciones de este trabajo son significativas. Se debe apoyar a los estudiantes que están aprendiendo inglés con estrategias de enseñanza actualizadas, en las cuales se tengan en cuenta sus fortalezas para permitirles tener éxito como aprendices de inglés.